Konteks Organisasi, Teknologi Informasi dan Kapabilitas Knowledge Sharing Pegawai di PT PLN (Persero) Area Palembang - Supardi Supardi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
Rapid changes in the information age indirectly require reforms in the public sector. The public sector must continue to improve, one of which is through the creation of innovation. Innovation in the public sector is carried out through the creation of ideas that cannot be separated from the knowledge sharing process. Knowledge sharing is important for organizations considering the nature of knowledge which is complementary and no single individual masters all fields of knowledge. Unfortunately, not many public agencies have implemented knowledge management properly through the use of information technology by considering organizational culture and the type of organizational structure. The purpose of this study was to examine how the influence of internalization of organizational culture and functional organizational structure on knowledge sharing capability at PT. PLN (Persero) Palembang Area by including information technology as an intervening variable. The method used in this study is a quantitative method using a questionnaire as primary data. The sample used in this study is a census sample so that the entire population is used as research respondents. The results showed that the use of information technology mediates the effect of internalization of organizational culture on knowledge sharing capabilities but does not mediate the effect of functional organizational structures on knowledge sharing capabilities. Based on these findings, the suggestions given by the researcher are: maximizing the use of information technology while maintaining a conducive organizational culture and climate for increasing knowledge sharing capabilities.